(untitled) (Sociología y tecnociencia, 2021)
Gigas for Schools promotes the design and development of social or business entrepreneurship projects with a technological base. This year, these projects were carried out by students in the 4th year of Secondary School, 1st year of Baccalaureate, Basic Vocational Training and Intermediate Vocational Training at 13 state-subsidised schools. In addition to the general objective of promoting entrepreneurship and technology, there is also the specific objective of encouraging female students’ interest in these fields. The results of the surveys carried out ad hoc point to an improvement in the assessment of female students with regard to entrepreneurship, but not so much with regard to technology.